SEED PRIMING WITH OIL CAKE EXTRACT IMPROVES THE GERMINATION OF BHENDI - R. VIJI; V. MANONMANI; N.VINOTHINI; R. K. BHAVYASREE; T. POOVARASAN (The Bioscan, 2021)
Seed priming with organic nutrients is now focused on using a macro or micronutrient enriched seeds. A study was conducted to evaluate the effect of seed priming with oil cake extracts on physiological seed quality parameters viz., speed of germination, germination per cent, root and shoot length, dry matter production and vigour index. Studies were carried out in bhendi cv. CO 1 to identify the suitable oil cake extracts and optimizing the concentration for seed priming for improving germination and vigour of bhendi. The extracts of oil cakes viz., groundnut, sesame, coconut, cotton and neem were used as seed priming agents for conducting the experiment. To optimize the concentration of oil cake extracts for seed priming treatment, the various concentrations viz., 5, 10, 15 and 20 % of each oil cake extracts were prepared and used. Among the different oil cake extracts, bhendi seeds primed with sesame oil cake extract 5 % was identified as the best suitable seed priming agent. In bhendi, sesame oil cake extract 5 % registered highest per cent of speed of germination, root and shoot length, dry matter production and vigour index over nonprimed seeds 73.6,4.5, 16.6, 31.2,35.2 and 33.3 %, respectively).